Designing Portable Circular Cutter Tools Using Inventors for Straight Cutting Iron at Welding Workshop - Abg Mohd Alwi, Abg Mohd Azri; Abdullah, Nurul Hidayah Liew; Lai, Chee Sern (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study was carried out with the aim of testing the design of the Portable Circular Cutter with Inventor for straight cutting at welding workshops. This study was performed to carry out the analysis of the product design strengths produced for the cutting process in the preparation of either steel plate or hollow steel. The Product Development Process Model is used as the basis for carrying out the design of this study product. This design model consists of five main phases: idea generation, idea refinement, concept development, product evaluation and product development. As this study uses Autodesk Inventor for designing the model, the concept development, product evaluation and product development are carried out within the application. This study uses the Finite Element Method found in the Autodesk Inventor application to test the design strength of the model being studied. Strengths in question are design endurance studied using Von Mises Stress, 1st Principal Stress, 3rd Principal Stress, Displacement and Safety Factor. The main value uesd is from Von Mises Stress which shows that the maximum force the design can accommodate before failure is 62.3218 MPa and the minimum Safety Factor is 4.3325 ul. In conclusion, the design of the Portable Circular Cutter Using Inventors for Straight Iron Cutting at Welding Workshop enables the work of cutting in the process of preparing the material to be carried out well and safely.